Scientific Basis for the Selection of Promising and New Mulberry Varieties on the Territory and in the Conditions of the Republic of Karakalpakstan. - Jiemuratov Elubay Bazarbaevich; Begdullaeva Jadira Bayrambaevna,; Doshniyazov Rasululla Berdaq uli; Eltaeva Aygerim Azat qizi (Zien Journals, 2023)
The article presents the scientific basis of breeding mulberry varieties in the conditions of Karakalpakstan. Based on the results of the analysis, the economic effect of the methods of breeding mulberry varieties is determined.
Keywords: organization; generative; vegetative method